Solitary wave impacts on vertical and overhanging near-coast structures. Issue 3 (3rd July 2018) - Huang, Mei; Kennedy, Andrew; Tomiczek, Tori; Westerink, Joannes
ABSTRACT: In this paper, we investigate short-duration solitary wave impacts on overhanging near-coast structures, which are represented here as rectangular blocks protruding out from a vertical wall. Wave transformation is computed for a variety of scenarios using the OpenFOAM variant IHFOAM. In agreement with previous studies, the largest pressures and loads occur when there is a violent impact with near-breaking or just-broken waves on the wall, causing a strong vertical jet. This condition most easily occurs with steep near-shore slopes. Maximum vertical loads on overhangs occur at significantly higher block elevations than are found for maximum horizontal loads. Overhang lengths have small effects on magnitudes of horizontal forces, but strongly increase positive uplift vertical loads. Although maximum instantaneous vertical loads can significantly exceed instantaneous horizontal loads, time-averaged vertical loads decrease rapidly with increasing averaging period while horizontal loads show more modest decreases; horizontal loads significantly exceed vertical loads for large averaging periods. This indicates that the pressure-impulse in the wall-generated vertical jets is much less than that arising from the horizontal solitary wave impacts.